Nursery of bonylip barb fish Osteochilus hasselti in an aquaponics system - Yani Hadiroseyani; Iis Diatin; Miftah Fajri Faozar; Apriana Vinasyiam (Jurnal Akuakultur Indonesia)
Bonylip barb fish Osteochilus hasselti is traditionally cultivated as a by-product in a polyculture system due to the problem of seed availability. The increase in local market demand for O. hasselti has not been met due to the low productivity of the growers. In an effort to increase the availability of fish seeds, intensification at the nursery stage has the potential to be effective in overcoming the limitations of land and water for cultivation. The aquaponic system can maximize yields through vertical use of space and also overcome water limitations with a recirculation system. This study aimed to evaluate the effectiveness of the aquaponics system on the intensification of O. hasselti nursery. The treatment tested was the stocking density of O. hasselti at an initial length of 4.28 ± 0.52 cm and a weight of 0.73 ± 0.29 g as many as 100 ind./m2, 150 ind./m2, and 200 ind./m2 in an aquaponic system with bok choy plants (Brassica rapa subsp. chinensis). Bonylip barb fish nursery for 30 days using aquaponic system showed that the treatment resulted in maximum survival with absolute length growth, feed conversion ratio, coefficient of variation in length and weight which were not significantly different (P>0.05). At densities above 100 ind./m2, the absolute weight growth value and the specific growth rate were higher. Overall, it can be concluded that the aquaponics system can be used for O. hasselti nursery at high stocking densities with the best production performance at a stocking density of 200 ind./m2.